BADANIE MOŻLIWOŚCI WYKORZYSTANIA ZOBRAZOWAŃ DYNAMICZNYCH (WIDEO) Z NISKIEGO PUŁAPU LOTNICZEGO (BSP) DO OPRACOWAŃ FOTOGRAMETRYCZNYCH - MŁYNARCZYK, ADAM; KRÓLEWICZ, SŁAWOMIR; RUTKOWSKI, PAWEŁ (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2019)
The use of unmanned aerial vehicles is becoming more and more popular for making high-altitude and orthophotomap models. In this process, series of images are taken at specific intervals, usually lasting several seconds. This article demonstrates the ability to make models and orthophotomaps from dynamic images – video recorded from UAV. The best mutual coverage of photographs was indicated (95–96%) and the photogrammetric process for joining images was presented, through the creation of a point cloud to obtain a digital terrain model and the orotfotomap. The data was processed in 150 different variants and the usefulness of this method was demonstrated. Problems and errors that may occur during the processing of recorded image data are also described.